Pengaruh Relasi Dalam Lingkungan Sosial Terhadap Pelaku Penyalahgunaan Narkoba - Mohammad Lutfi; Bobsaid, Yasmin; Airlangga Rizki Putra; Siti Noorhalisa; Aditya Sangga Buana Richter; Kevin Saputra (JURNAL ILMIAH RESEARCH STUDENT, 2025)
The social environment often influences someone who falls into drug use, including the influence of peers and the social norms that develop around them. This research was conducted with the aim of understanding more deeply how the social environment influences drug doctrine behavior. This research uses a qualitative method with a phenomenological approach, which aims to understand in depth the detrimental behavior in cases of drug transmission. Research conducted at the Cipinang Class 1 Correctional Institution found that the source with the initials AS provided information that he initially only saw friends who used drugs. After that, curiosity arose within AS to try drugs and find out how to make and distribute them.